Linking sustainability to the healthy eating patterns of the Dietary Guidelines for Americans: a modelling study - Nicole Tichenor Blackstone, PhD (The Lancet Planetary Health, 2018)
Summary: Background: Evidence-based nutrition policy is a key mechanism to promote planetary health. In the USA, the Dietary Guidelines for Americans are the foundation of nutrition policy and guide more than US$80 billion in federal spending. Recent attempts have been made to incorporate sustainability into the development of the Dietary Guidelines. However, the sustainability of the 2015–20 Dietary Guidelines remains unclear; research has not yet assessed the environmental impacts of the distinct healthy patterns recommended by the policy. Methods: In this modelling study done at the University of New Hampshire (Durham, NH, USA), we analysed the healthy US-style (US), healthy Mediterranean-style (MED), and healthy vegetarian (VEG) patterns recommended in the 2015–20 Dietary Guidelines for Americans. Food groups and subgroups consisted of 321 commonly consumed foods, with group composition predetermined by the US Department of Agriculture. We compiled and used multiple datasets to assign environmental burdens to foods, focusing on six impact categories of policy importance: global warming potential, land use, water depletion, freshwater and marine eutrophication, and particulate matter or respiratory organics. We did life cycle impact assessments for each of the three diet patterns and compared the six impact categories between the patterns. We also analysed the proportion contribution of the food groups to each impact category in each of the diet patterns. Findings: The US and MED patterns had similar impacts, except for freshwater eutrophication. Freshwater eutrophication was 31% lower in the US pattern than the MED pattern, primarily due to increased seafood in the MED pattern. All three patterns had similar water depletion impacts, with fruits and vegetables as major contributors. For five of the six impacts, the VEG pattern had 42–84% lower burdens than both the US and MED patterns. Reliance on plant-based protein and eggs in the VEG pattern versus emphasis on animal-based protein in the other patterns was a key driver of differences, as was a lower overall protein foods recommendation in the VEG pattern. Interpretation: The recommended patterns in the Dietary Guidelines for Americans might have starkly different impacts on the environment and other dimensions of human health beyond nutrition. Given the scale of influence of the Dietary Guidelines for Americans on food systems, incorporating sustainability into their development has the potential to have great benefit in terms of long-term food security. Funding: None.